Uma proposta para tratamento de respostas ao acaso em avaliações utilizando o raciocínio estatístico e lógica difusa - Bento, Antônio Carlos (2015)
The research focuses on the performance evaluation methodology within the models of multiple-choice questions from methodeutics criteria of Fuzzy Logic proposed by Lotfi Zadeh associated with statistical reasoning presented by Santos, Pigari and Tolentino present in the theories of uncertainty discussed by Russell and Norvig and item response theory presented by Fontanive. The study was based on an exploratory and experimental research used questionnaires that were submitted to academic groups. The collected data were compared with a bibliography on the field evaluation, education and logic, resulting in the organization of a methodology that enabled the construction of a prototype computer system to validate the realized and expected outcomes studies. Following the classification s heuristics Clancey it concludes by identifying a set of rules that have been identified as strong enough to guide work and software modeling, aimed at building models of multiple-choice questions based Fuzzy Logic rules. Finally, the results were gathered and presented by means of a system prototype able to characterize the main established rules, as well as studies, being able to be fully utilized in the implementation of performance assessments that may present evidence with expected results, supporting identifying random responses during evaluations